EXPLORING THE ROLE OF INVESTMENT IN DRIVING ECONOMIC GROWTH: A CASE STUDY OF THE BANGKA BELITUNG ISLANDS - PUTRA, AGUNG RIZKI; Samssudin, M. Afdal; Hamsani, Hamsani; Akbar , M.Faisal; Rahmadoni, Firman; Wulandari, Ayu (Ekonomi dan Bisnis, 2023)
The economic growth of a region is significantly influenced by various factors, among which investment and consumption are considered pivotal. Despite the considerable focus on these aspects in existing literature, there is a noticeable gap in understanding their impact, particularly in the context of Indonesia's Bangka Belitung Islands. This research aims to fill this gap by empirically investigating the multiplier effect of investment on economic growth in this region. By employing the Random Effect Model (REM) on logarithmically transformed data, the study attempts to offer nuanced insights into the relationship between consumption, investment, labor, and economic growth. The findings and their implications are expected to guide policy decisions and stimulate balanced and inclusive economic growth across Indonesia. The findings diverge from certain previous studies that found no significant relationship between investment and economic growth, particularly in regions outside Java. These discrepancies could be attributed to variations in data sources, temporal spans, and methodologies employed across these studies. Additionally, the research underscores the critical role of infrastructure in regional economic growth, echoing the emphasis found in the extant literature. In conclusion, the study reinforces the importance of Consumption and Investment in driving economic growth in the Bangka Belitung Islands. It further urges policymakers to prioritize balanced investment and infrastructure development, especially in regions beyond Java, to encourage more equitable economic growth across Indonesia.